2008
DOI: 10.1042/bj20070891
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits FtsZ assembly: an attractive mechanism for its antibacterial activity

Abstract: The assembly and stability of FtsZ protofilaments have been shown to play critical roles in bacterial cytokinesis. Recent evidence suggests that FtsZ may be considered as an important antibacterial drug target. Curcumin, a dietary polyphenolic compound, has been shown to have a potent antibacterial activity against a number of pathogenic bacteria including Staphylococcus aureus, Staphylococcus epidermidis and Enterococcus. We found that curcumin induced filamentation in the Bacillus subtilis 168, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
322
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 446 publications
(331 citation statements)
references
References 41 publications
9
322
0
Order By: Relevance
“…In agreement with our study, Rai et al, suggested that curcumin might be considered as an important antibacterial drug target. In this study, curcumin has been shown to have a potent antibacterial activity against a number of pathogenic bacteria including Staphylococcus aureus, Staphylococcus epidermidis and Enterococcus (32). Also, Wang et al used microcapsule curcumin against Staphylococcus aureus, Escherichia coli, Yersinia enterocolitica, Bacillus subtilis and Bacillus cereus.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our study, Rai et al, suggested that curcumin might be considered as an important antibacterial drug target. In this study, curcumin has been shown to have a potent antibacterial activity against a number of pathogenic bacteria including Staphylococcus aureus, Staphylococcus epidermidis and Enterococcus (32). Also, Wang et al used microcapsule curcumin against Staphylococcus aureus, Escherichia coli, Yersinia enterocolitica, Bacillus subtilis and Bacillus cereus.…”
Section: Discussionmentioning
confidence: 99%
“…16 This may be due to a direct increase in the GTP hydrolysis reaction, induced by the change in FtsZ secondary structure on curcumin binding. Alternatively, the increase in GTP turnover may be due to a steric hindrance on polymer bundling (which is not explicitly represented in our model).…”
Section: Bacillus Subtilis Cell Cultures Its Mode Of Action Is Via Dmentioning
confidence: 99%
“…The results of GTPase assay indicated that the interaction of curcumin with FtsZ enhanced the GTPase activity but destabilized the FtsZ polymers [81]. Using computational docking, Roy and co-workers identified the possible binding sites of curcumin in E. coli FtsZ and B. subtilis FtsZ.…”
Section: Curcuminmentioning
confidence: 99%